'We want to know more than that': lessons learnt from the public workshop on collections data at the V&A. (4th March 2023) - Park, Juhee
ABSTRACT: This study challenges institutionalised collection and documentation practices at museums, providing a space for the reconfiguration of concepts and boundaries of collections data with respect to digital objects in particular. While various technology-driven approaches have been introduced for the management of collections data, little attention has been given to the nature of collections data and how museums can gather them to improve plurality. As part of the experimental project titled Content/Data/Object at the Victoria and Albert Museum (V&A) in London, this research analyses the public workshop wherein participants discussed a digital object at the museum (i.e., Minecraft) as a case study and proposes a conceptual framework with expanded concepts of collections data and possible documentation methods. It provides museums with a dynamic model to diversify collections data that is able to reflect the various needs of the public and allow the interpretation of our heritage to flourish.